Changes to taxonomy and the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2017) - Adams, Michael J.; Lefkowitz, Elliot J.; King, Andrew M. Q.; Harrach, Balázs; Harrison, Robert L.; Knowles, Nick J.; Kropinski, Andrew M.; Krupovic, Mart; Kuhn, Jens H.; Mushegian, Arcady R.; Nibert, Max; Sabanadzovic, Sead; et al. (Archives of virology, 2017)
This article lists the changes to virus taxonomy approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in March 2017.This article lists the changes to virus taxonomy approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in March 2017.